1990
DOI: 10.1177/154193129003401906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Image Polarity on VDT Task Performance

Abstract: Three experiments were conducted in which positive and negative contrast on visual display terminals were directly compared. Operator tasks included visual search and reading, with accuracy and timeliness of response measured. In all cases where significant differences exist, better performance was obtained with negative contrast (dark characters or symbols on a lighter background). The increases in performance range from a low of 2.0 percent to a high of 31.6 percent. Based on the above results, we believe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 1 publication
2
11
1
Order By: Relevance
“…Lobe shapes mapped in the positive polarity condition were larger, rounder and more regular than those mapped in the negative polarity condition. These results may go some way to account for previous findings that visual search performance was significantly better with positive polarity stimuli (Snyder et al 1990, Shen et al 2009). The greater ability of participants to identify targets under positive polarity conditions may also be attributed to the widespread use and familiarity with reading the dark characters on white background used in most printed materials and visual displays.…”
Section: Display Polaritysupporting
confidence: 49%
See 1 more Smart Citation
“…Lobe shapes mapped in the positive polarity condition were larger, rounder and more regular than those mapped in the negative polarity condition. These results may go some way to account for previous findings that visual search performance was significantly better with positive polarity stimuli (Snyder et al 1990, Shen et al 2009). The greater ability of participants to identify targets under positive polarity conditions may also be attributed to the widespread use and familiarity with reading the dark characters on white background used in most printed materials and visual displays.…”
Section: Display Polaritysupporting
confidence: 49%
“…However, some research on display polarity and visual performance showed that, stimulus polarity had no effect on visual acuity and subjective ratings (Wang and Chen 2000). Snyder, et al (1990) compared VDT task performance under positive and negative polarities and showed that performance under negative polarity was better. There was also evidence that negative polarity yielded marginally better visual acuity than positive polarity, with an overall white-on-black to black-on-white Snellen fraction ratio of 1.043 (Westheimer et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…For example, Saito et al 13 found that black objects on a white background were the best for VDT display types. However, Snyder et al 17 proposed that better visual performance was found with white objects on a black background. Thus, this study tried to find out if there was a relationship between Mura detection and polarity.…”
Section: Defined a New Regression Equation Between The Human Eyes Andmentioning
confidence: 99%
“…However, other studies yielded no significant difference between the two polarities (Shieh, 2000;Wang & Chen, 2003). Snyder, Decker, Lloyd, and Dye (1990) measured the performance of operators in accuracy and response time (RT) in visual search and reading tasks performed under positive and negative polarity settings. Analyses showed that performance with negative polarity is either equal to or better than that of positive polarity.…”
Section: Display Polaritymentioning
confidence: 99%